Pengaruh Experiential Marketing Terhadap Loyalitas Pelanggan Pada Coffee Shop Desa Wisata Tuk Tuk Siadong Kabupaten Samosir - Masditou Adit (Politeknik Pariwisata Medan, 2023)
This study aims to investigate the impact of Experiential Marketing on customer loyalty at a coffee shop located in Tuk Tuk Siadong Tourism Village, Samosir Regency. Experiential Marketing is a marketing approach that aims to create a unique and satisfying experience for customers. In the context of a coffee shop, positive experiences include factors such as a comfortable atmosphere, friendly service, special activities, and a pleasant environment. The research method used was a survey using a questionnaire distributed to coffee shop customers as respondents. The collected data were analyzed using regression analysis techniques to identify the relationship between the positive experience provided by the coffee shop and the level of customer loyalty. The results of the study show that there is a significant relationship between the positive experiences provided by coffee shops and customer loyalty. Customers who experience unique and satisfying positive experiences tend to have higher levels of loyalty to the coffee shop. Factors such as a comfortable atmosphere, friendly service, and special activities contribute to a positive experience and influence customer loyalty. The implication of this study is that coffee shops in Tuk Tuk Siadong Tourism Village need to pay special attention to the positive experiences they provide to customers. They need to create a comfortable atmosphere, improve service quality, and present interesting special activities. By engaging customers in a unique experience, coffee shops can strengthen customer loyalty and create a competitive advantage in the marketplace. This research contributes to the understanding of the importance of Experiential Marketing in creating positive experiences that have an impact on customer loyalty in coffee shops. The results of this study can be the basis for coffee shop business owners to plan marketing strategies that focus on a unique and satisfying customer experience.